Measurement properties of the ASAS Health Index: results of a global study in patients with axial and peripheral spondyloarthritis - DURUÖZ, MEHMET TUNCAY (BMJ PUBLISHING GROUP, 2018)
Objectives To evaluate construct validity, interpretability, reliability and responsiveness as well as determination of cut-off points for good and poor health within the original English version and the 18 translations of the disease-specific Assessment of Spondyloarthritis international Society Health Index (ASAS HI) in 23 countries worldwide in patients with spondyloarthritis (SpA). Methods A representative sample of patients with SpA fulfilling the ASAS classification criteria for axial (axSpA) or peripheral SpA was used. The construct validity of the ASAS HI was tested using Spearman correlation with several standard health outcomes for axSpA. Test-retest reliability was assessed by intraclass correlation coefficients (ICCs) in patients with stable disease (interval 4-7 days). In patients who required an escalation of therapy because of high disease activity, responsiveness was tested after 2-24 weeks using standardised response mean (SRM). Results Among the 1548 patients, 64.9% were men, with a mean (SD) age 42.0 (13.4) years. Construct validity ranged from low (age: 0.10) to high (Bath Ankylosing Spondylitis Functioning Index: 0.71). Internal consistency was high (Cronbach's alpha of 0.93). The reliability among 578 patients was good (ICC=0.87 (95% CI 0.84 to 0.89)). Responsiveness among 246 patients was moderate-large (SRM=-0.44 for non-steroidal anti-inflammatory drugs, -0.69 for conventional synthetic disease-modifying antirheumatic drug and -0.85 for tumour necrosis factor inhibitor). The smallest detectable change was 3.0. Values <= 5.0 have balanced specificity to distinguish good health as opposed to moderate health, and values >= a12.0 are specific to represent poor health as opposed to moderate health. Conclusions The ASAS HI proved to be valid, reliable and responsive. It can be used to evaluate the impact of SpA and its treatment on functioning and health. Furthermore, comparison of disease impact between populations is possible.
Keywords: SOCIETY CLASSIFICATION CRITERIA; ANKYLOSING-SPONDYLITIS; PHYSICIAN DISCORDANCE